Peningkatan Kapasitas Aparatur Kampung dalam Penyelesaian Sengketa Perdata melalui Mediasi di Distrik Walesi Kabupaten Jayawijaya Provinsi Papua Pegunungan - Irna, Irna; Wijaya, Mohammad Safrul; Marian, Simon; Wenda, Ben (LPPM ITB AAS Indonesia Surakarta, 2024)
This community service initiative aims to enhance the capacity of village officials in resolving civil disputes through mediation methods. Villages, also known as kampungs, frequently encounter various types of civil disputes, such as land disputes, inheritance issues, and contract disagreements, which require fair and peaceful resolution. However, insufficient understanding and skills in mediation often result in ineffective dispute resolution and the potential for further conflict. This program involves intensive training for village officials in the Walesi District on the fundamentals of civil law, mediation techniques, and effective communication skills. The training is conducted through a series of workshops, simulations, and case studies designed to provide a practical and comprehensive understanding of the mediation process. Additionally, the program offers guide materials and training modules that can serve as references for village officials in their duties. The results of this initiative demonstrate a significant improvement in the understanding and skills of village officials in managing civil disputes through mediation. Trained officials are now able to resolve disputes more effectively, reduce tensions among residents, and foster a more harmonious environment. This initiative is expected to serve as a model for other villages or kampungs in developing their capacity for independent and peaceful civil dispute resolution. Keywords: Mediation, Civil Law, Dispute Resolution, Village Official Capacity